The approximation of bivariate functions by bivariate operators and GBS operators - Pop, Ovidiu T. (Rev. Anal. Numér. Théor. Approx., 2011)
In this paper we demonstrate a general approximation theorem for the bivariate functions by bivariate operators and GBS (Generalized Boolean Sum) operators.